O novo começo feminino em metade cara, metade máscara, de Eliane Potiguara - Montado, Valéria Caroline do Amaral (2021)
This paper presents an analysis of the work Metade cara, metade máscara, by Eliane Potiguara, in order to reflect on the intention of the New Beginning, according to Hannah Arendt's proposal, resumed by the theorist Julia Kristeva. In order to support the importance of indigenous literature, the work O Romantismo no Brasil, written by Antônio Candido, was used. From this work, one can see the literary erasure suffered by the original people over the centuries. It is observed that the indigenous literature still occupies few spaces, that is why the Indigenous cultures are still little known, resulting in a caricature of the indigenous created even in the romantic period, mainly with regard to the image of the woman. Through this literature, which has proved to be a powerful tool, it is possible to rescue the ancestry of the Indigenous peoples and create a range for the perpetuation of their cultures. Thus, looking for the New Beginning in a work written by an Indigenous woman aims to bring up for discussion the Indigenous experiences and the importance of the female role in Amerindian culture, identifying the potential for creative power that exists in the Indigenous community. Key-words: Eliane Potiguara; Hannah Arendt; Indigenous literature; New Beginning.